2016
DOI: 10.1016/j.adolescence.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

The effects of parental mental health and social‐emotional coping on adolescent eating disorder attitudes and behaviors

Abstract: This study examined whether social-emotional coping skills moderate the association between parental mental health symptoms and adolescent disordered eating attitudes and behaviors in a clinical sample of adolescents with internalizing and/or externalizing symptoms. Fifty-nine adolescent-parent dyads (N = 118 total participants) recruited from a metropolitan area in the Northeastern United States completed assessments at baseline and 12-month follow-up. Generally, higher parental depression and anxiety were on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
0
10
1
Order By: Relevance
“…Further, emotion dysregulation moderated the relationship between alcohol use and eating pathology for excessive exercise and cognitive restraint; however, greater alcohol use was associated with lower eating pathology at high levels of emotion dysregulation, and greater alcohol use was associated with higher eating pathology at low levels of emotion dysregulation. Together, these results contradict theory and previous literature that shows that higher levels of various psychopathology (e.g., negative affect, body image concerns, and parental anxiety) is associated with greater eating pathology (e.g., dietary disinhibition, binge eating, purging) when one experiences more difficulties regulating emotions (Luadlai et al, 2018;Hughes & Gullone, 2011;Martinson et al, 2016).…”
contrasting
confidence: 90%
“…Further, emotion dysregulation moderated the relationship between alcohol use and eating pathology for excessive exercise and cognitive restraint; however, greater alcohol use was associated with lower eating pathology at high levels of emotion dysregulation, and greater alcohol use was associated with higher eating pathology at low levels of emotion dysregulation. Together, these results contradict theory and previous literature that shows that higher levels of various psychopathology (e.g., negative affect, body image concerns, and parental anxiety) is associated with greater eating pathology (e.g., dietary disinhibition, binge eating, purging) when one experiences more difficulties regulating emotions (Luadlai et al, 2018;Hughes & Gullone, 2011;Martinson et al, 2016).…”
contrasting
confidence: 90%
“…Parenting (Alfiasari et al, 2011;Schoppe-Sullivan, 2017;Ren & Xu, 2019). Risky behavior/aggressiveness (Martinson et al, 2016;Tsabedze et al, 2019). Online social networking (Tyagi & Meena, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…25 Social support can significantly predict the emotional behaviour of adolescents, and higher social support has a protective effect on adolescent mental health. 26 Researchers have shown that the relationship between social support and self-concept is stable and positively correlated. There is a difference between social support factors and the correlation between the fractal dimensions of self-concept.…”
Section: Introductionmentioning
confidence: 99%